Formulation and evaluation of antimicrobial herbosomal gel from Quercus infectoria extract - W. Y, Suzilla; A., Izzati; I, Isha; A., Zalina; V. K., Rajaletchumy (Institute of Physics Publishing, 2020)
Nowadays, the use of herbal medicine is gaining importance for treating many diseases due to their significant effect and lesser side effects as compared to allopathic medicines. Phytosomal herbal formulations or herbosomes are better absorbed and produce better bioavailability than the conventional botanical extracts. Hence, this study is conducted to formulate the herbosomal gel from QI galls ethanolic extract. The QI gall was extracted using ethanol giving the percentage of yield 17%. For the High-Performance Liquid Chromatography analysis, it was revealed that the QI galls extract contains large amount of tannic acid (1794.18 mg/g) and small amount of gallic acid (76.22 mg/g). The formulation consists of 1.0% of Carbopol 940 were found to be the best formulation since it shows good physicochemical properties. pH value was 6.31 while the viscosity was 3482.3144 cps. Formulated gel showed good stability after 21 days of formulation by not showing significance changes in pH value, viscosity and spreadability. Disc diffusion method was used to determine the antimicrobial activity and the results showed the inhibition zone for P. aeruginosa was greater than S. aureus. As conclusion, the QI galls extract formulated herbosomes was showed promising results to be developed as a new antibacterial gel formulation.